IMPORTANCE PERFORMANCE ANALYSIS SEBAGAI ANALISIS TOTAL QUALITY MANAGEMENT (TQM) APOTEK KIMIA FARMA DI KOTA SEMARANG - Ratna Wulandari; Insyiroh Nur Hidayati (VISIKES: Jurnal Kesehatan Masyarakat, 2022)
The quality of the pharmaceutical services provided by a pharmacy greatly determines the success of the competition in fulfilling the patient's satisfaction and is one of the important things to determine the strategy of developing the business and maintaining the quality of the pharmacy itself. Total Quality Management (TQM) is a management system that is used to improve the quality of services and to help achieve the target that is established by an organization.  This research is an observational research by using interviews through questionnaires conducted in 27 outlets of pharmacy Kimia Farma that exist in Semarang City with the aim to analyze the implementation of Total Quality Management in its pharmaceutical service. Data analysis is performed using the Importance Perfomance Analysis (IPA) method. In establishing a pharmacy development strategy, a Focus Group Discussion (FGD) was conducted to analyse internal and external factors of Kimia Farma Pharmacy with SWOT analysis. IPA evaluation results show average performance value of 4.05 and average importance value of 4.31 as well as average level of conformity of all components by 93.87%. Then it can be said that the implementation of TQM at the Kimia Farma pharmacy in Semarang has been running well. Development strategy that can be done based on SWOT analysis is SO (Strengths-Oportunity) strategy to optimize the resources owned and maximize the success of opportunities that exist in the purpose of improving the performance of the Kimia Farma pharmacy in Semarang.Keywords: Total Quality Management, pharmacy services, strategy, Important Performance Analysis, SWOT